Rancangan Bangun Prototipe Monitoring dan Kontrol Pompa Air Pengisian Tandon Air Tempat Wudhu Dengan Sumber Air Sumur Gali - Chandra, Yudi; Radwitya, Erick; suwanda, Ivan (entries, 2024)
Water plays an important role in the survival of living things on earth. Water will be very useful for life on earth, one of which is a place of worship for Muslims. Almost all places of worship use reservoirs to store water, but not all places of worship get water sources from the Regional Drinking Water Company (PDAM), one of which is the Ashabul Yamin Mosque located in Suka Maju Village. The mosque administrators must wait while the water reservoir is filled to control the fullness of the water in the reservoir and also the dryness of the water in the dug well which can damage the water pump. From the results of the discussion, a desire arose to facilitate / lighten the work of the mosque administrators by conducting research on monitoring and controlling the water pumps used so that when the reservoir is full the pump will turn off and if the water in the dug well is empty the pump will also turn off. The stages carried out to achieve the expected goals are conducting literature studies, designing software and hardware, assembling prototypes and conducting testing. The target of this research result is a prototype of water pump monitoring and control in the form of 2 water reservoirs, 1 as a water source and 1 as a water tank, the pump will work when the water in the water tank contains 20% and above and the water in the water source contains 50% and above and the pump will turn off when the water in the water tank is full (100%) or the water in the water source is in 20% condition. This research is expected to be implemented directly in the Ashabul Yamin Mosque, Suka Maju Village